Síntese de heterociclos: 2-alquil/arilcalcogeno-n-(4-aril-1,3-tiazol-2-il)acetamidas e (s)-n-(1-(3-aril-1,2,4-oxadiazol-5-il)alquil)-2-(calcogenofenil) acetamidas derivados de organocalcogênios - Wolf, Lucas (2015)
In the present work, a series of 2-alkyl/arylchalcogenide-N-(4-aryl-1,3-thiazol-2-yl)acetamide was prepared via addition of aryl or alkyl chalcogenides. This methodology allowed the preparation of new derivatives of 2-amino-1,3-thiazoles in good yields. The compound synthesized is intended to evaluate the biological potential from the antioxidant activity by scavenging capacity of the assay by ABTS and DPPH. Was also developed a methodology for obtaining the compounds (S)-N-(alkyl-1-(3-aryl-1,2,4-oxadiazol-5-yl)-2-(phenylchalcogenide)acetamide derived from (S)-2-(2-(phenylchalcogenide)acetamido)alkanoic acids and arylamidoximes employing microwave irradiation. This synthesis was carried out in three conditions by varying the reaction time, temperature and solvent. The reactions employing microwave irradiation exhibit advantages against reactions using conventional method. These compounds were characterized by 1H NMR, 13C NMR and techniques high resolution mass spectrometry.